Theoretical Review on The Graduate Attributes and The Readiness for Employability Among Engineering Graduates in The Higher Education Institutes (HEIs) in Oman - Hinai, Masoud Rashid Al; Bhuiyan, Abul Bashar; Husin, Nor Azilah (Indian Journal of Finance and Banking, 2020)
The Omani higher education system has enlarged noticeably since 1970 both in the number of students and in the infrastructure.  As a result, there has been a big investment to provide quality higher educational institutes capable of providing suitable graduates to fulfill the requirements of the labor. The mean purpose of the higher education system is to provide the nation with the quality education that meets the requirements of the 21st century with graduates having readiness for employability skills and competencies. However, The skills gap between HEIs graduates and industrial requirements in Oman and other regional Gulf countries is seen as one of the most important factors that affect the employment of graduates in the private sector because the graduate readiness for employability did not consider the graduate attributes factors which influence graduate readiness for employability. Therefore, the main objective of the current study is to determine the effects of the graduates’ attributes on the readiness for employability and justified with existing theories in the higher educational institutes in Oman. Specifically, this study intends to determine the influencing factors that contribute to the readiness of Engineering Graduates for Employability in the Higher Education Institutes (HEIs) in Oman. The study reviews the current literature on the effects of graduates’ attributes on the readiness for employability especially for Omani engineering graduates as the main source of information. The study is designed to determine and analyze graduates’ attributes factors and elements. The literature utilized for this study covers the latest literature (from 2013 to 2019) extracted from Google Scholar, ProQuest, and Scopus. The four main keywords used were ‘higher education’, ‘graduate attributes ‘or ‘readiness for employability, and ‘skills gap and justify with most relevant theories in the particular area’. The study summarized the empirical review on the graduate attributes which analyses the effects of graduate attributes on the graduates’ readiness for employability that will be considered as an empirical study on the graduates of the engineering colleges in Oman. The study explored review findings on the graduate readiness for employability framework from different graduates’ attributes and provisions perspectives. The results of the study will fill the gap in understanding the main graduate attributes factors affecting the attainment of graduates’ readiness for employability skills which has justified with most relevant theories in the particular. The study also recommends a policy guideline for ensuring of readiness of engineering graduates for employability in the HEIs in Oman.